Risk of hepatitis B reactivation in patients treated with direct-acting antivirals for hepatitis C - Aggeletopoulou, Ioanna (World J Gastroenterol, 2017)
The recent introduction of direct-acting antiviral drugs (DAAs) for treatment of the hepatitis C virus (HCV) has greatly improved the management of HCV for infected patients. These viral protein inhibitors act rapidly, allowing HCV clearance and increasing the sustained virological response rates. However, hepatitis B virus (HBV) reactivation has been reported in HCV/HBV co-infected patients. Hepatitis B reactivation refers to an abrupt increase in the HBV and is well-documented in patients with previously undetected HBV DNA due to inactive or resolved HBV infection. Reactivation can occur spontaneously, but in most cases, it is triggered by various factors. Reactivation can be transient, without clinical symptoms; however, it usually causes a hepatitis flare. HBV reactivation may occur regardless of HCV genotype and type of DAA regimen. HBV screening is strongly recommended for co-infected HCV/HBV patients before initiation and during DAA therapy regardless of HBV status, HCV genotype and class of DAAs used. HBV reactivation can be prevented with pretreatment screening and prophylactic treatment when necessary. Additional data are required to evaluate the underlying mechanisms of HBV reactivation in this setting.